The private sector and organized crime: criminal entrepreneurship, illicit profits, and private sector security governance - Zabyelina, Yuliya; Thachuk, Kimberley L.; Savona, Ernesto Ugo (Routledge studies in organised crime, 2023)
"This book contributes to the literature on organized crime by providing a detailed account of the various nuances of what happens when criminal organizations misuse or penetrate legitimate businesses. It advances the existing scholarship on attacks, infiltration, and capture of legal businesses by organized crime and sheds light on the important role the private sector can play to fight back. It considers a range of industries from bars and restaurants to labour-intensive enterprises such as construction and waste management, to sectors susceptible to illicit activities including transportation, wholesale and retail trade, and businesses controlled by fragmented legislation such as gambling. Organized criminal groups capitalize on legitimate businesses beleaguered by economic downturns, government regulations, natural disasters, societal conflict, and the COVID-19 pandemic. To survive, some private companies have even become the willing partners of criminal organizations. Thus, the relationships between licit businesses and organized crime are highly varied and can range from victimization of businesses to willing collusion and even exploitation of organized crime by the private sector - albeit with arrangements that typically allow plausible deniability. In other words, these relationships are highly diverse and create a complex reality which is the focus of the articles presented here. This book will appeal to students, academics, and policy practitioners with an interest in organized crime. It will also provide important supplementary reading for undergraduate and graduate courses on topics such as transnational security issues, transnational organized crime, international criminal justice, criminal finance, non-state actors, international affairs, comparative politics, and economics and business courses"--